An Error Analysis of Students’ Translating Tenses at SMK Pasundan 2 Cianjur - Andarisa, Wulan Dara (Universitas Suryakancana, 2018)
Abstract The title of this paper is “An Error Analysis of Students’ Translating Tenses”. The goal of this research are to find out the kind of errors do the students commonly make in English-Indonesian translation, especialy in tenses and to find out the causes of their errors in English-Indonesian translation tenses. The method that the writer used in this research was descriptive qualitative as its method to analyze and describe entire data. The research participants of this study was the member of grade XII T-Eind’s Class at SMK 2 Pasundan Cianjur. The member of partisipants consisits of 47 male students. The data was taken from translation test and interview. After getting entire the data, then it was analyzed and describe it. Then after analyzing them, the writer found the kind of errors when students’ translating tenses. such as translation verb, translation to be, translation of “be”, translation of plural word and the unsuitable dictions of transfer the words from SL to TL in tenses. Based on the analysis the error when students translated verb in tenses consists of 83 erors from 423 data, the error when students translated to be in tenses consists of 53 errors from 423 data, the error when students translate “be” in tenses consists of 35 errors from 423 data, the error when translation plural of word consist of 8 errors from 423 data, and the unsuitable diction of translfer the word from SL to Tl in tenses consists of 37 erors from 423 data. Moreover the causes of students errors when they translated tenses are translation used word to word method, the students have not a good source language (English language), the students have not a good comprehension of vocabulary and the students not understand about tenses (present continuous tense, past continuous tense and future countinuous tense). Some suggestions was given to develop the learners’ competence and the reseacher hoped this study benefit for others reseachers as futhermore reference. Keywords: translating, tenses, an error analysis.